Parascheva of Tirnovo in the Russian Variant of Service – „Monarchical” Image of Holiness - Kuczyńska, Marzanna (Poznańskie Studia Slawistyczne, 2013)
The article discusses the specific of sanctity of Parascheva of Tirnovo in the Russian Orthodox Church, an anchoress the most venerated by the Eastern Church. The pattern of holiness formed in the late nineteenth century is far richer and deeper than in other Slavic Orthodox churches. It is based on the Trinitarian, Christological, Marian themes, as well as on the strict hesychastic asceticism proper for hermits. The functions of the saint are also wider – she serves as a teacher, protector, defender, guardian of the state, the highest authorities (tsar) and the faithful – which is not typical for the sanctity of women, but rather for the holy hierarchs, bishops as pastors of the Church and the nation.